Bioresources and Bioprocessing - Xu, Jian-He
Bioresources and Bioprocessing (BIOB) is a peer-reviewed open access journal published under the brand SpringerOpen. BIOB aims at providing an international academic platform for exchanging views on and promoting research to support bioresource development, processing and utilization in a sustainable manner. As an application-oriented research journal, BIOB covers not only the application and management of bioresource technology but also the design and development of bioprocesses that will lead to new and sustainable production processes. BIOB publishes original and review articles on most topics relating to bioresource and bioprocess engineering, including: Biochemical and microbiological engineering Biocatalysis and biotransformation Biosynthesis and metabolic engineering Bioprocess and biosystems engineering Bioenergy and biorefinery Cell culture and biomedical engineering Food, agricultural and marine biotechnology Bioseparation and biopurification engineering Bioremediation and environmental biotechnology.